2002
DOI: 10.1006/qres.2002.2383
|View full text |Cite
|
Sign up to set email alerts
|

Saharan Dust Transport and High-Latitude Glacial Climatic Variability: The Alboran Sea Record

Abstract: Millennial to submillennial marine oscillations that are linked with the North Atlantic's Heinrich events and Dansgaard–Oeschger cycles have been reported recently from the Alboran Sea, revealing a close ocean-atmosphere coupling in the Mediterranean region. We present a high-resolution record of lithogenic fraction variability along IMAGES Core MD 95-2043 from the Alboran Sea that we use to infer fluctuations of fluvial and eolian inputs to the core site during periods of rapid climate change, between 28,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
164
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(184 citation statements)
references
References 44 publications
18
164
1
1
Order By: Relevance
“…Previous studies revealed the presence of five different Fusarium species in the river and sea water of southeastern Spain [23]. Fluvial sediments transport was proposed as the primary route for the transportation of lithogenic and fungal particulates to the Alboran Sea [20,24]. The results presented here allow us to speculate on a new source of inoculum for Fusarium genus: atmospheric dust, which can fall down directly or together with rain.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies revealed the presence of five different Fusarium species in the river and sea water of southeastern Spain [23]. Fluvial sediments transport was proposed as the primary route for the transportation of lithogenic and fungal particulates to the Alboran Sea [20,24]. The results presented here allow us to speculate on a new source of inoculum for Fusarium genus: atmospheric dust, which can fall down directly or together with rain.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, palaeoenvironmental research indicates that stable conditions in the northwest African area over a time span of more than 10 ka would not be expected. Thus, a strong influence of climatic cycles like Heinrich-events and D-O cycles occurring with a high frequency of some ka on this region is reported from several studies (Cacho et al, 1999;Moreno et al, 2002, Moreno andCanals 2004), which play an important role in this geomorphic environment instable even during generally wetter periods. Furthermore, high electric conductivity of the sediments (e.g.…”
Section: Scenario IImentioning
confidence: 72%
“…Close to the continent, the sediments are generally coarser grained compared with the distal open ocean. Most deep-sea cores recovered within hundreds of kilometers off continents are characterized by fine-grained aeolian dust (2-4 μm; e.g., Boven and Rea, 1998;Rea and Hovan, 1995), while several deep- sea sediment studies located relatively close to the continent showed that aeolian dust fallout is characterized by terrigenous sediment with a modal grain size larger than 6 μm (e.g., Koopmann, 1981;Holz et al, 2004;Moreno et al, 2002;Stuut et al, 2002). This is supported by the coarse silt sized of present-day dust samples from the Namib Desert collected along transect from the coast to the core Site at MD 962094, Walvis Ridge (Stuut et al, 2002).…”
Section: Long-term Modes and Major Shifts In Sedimentation Patternsmentioning
confidence: 99%